2019
DOI: 10.3390/children6070084
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of a Yoga Breathing Practice on Attention and Anxiety in Pre-Teen Children

Abstract: Pre-teen children face stressors related to their transition from childhood to adolescence, with a simultaneous increase in academic pressure. The present study compared the immediate effects of 18 min of (i) high frequency yoga breathing with (ii) yoga-based breath awareness and (iii) sitting quietly, on (a) attention and (b) anxiety, in 61 pre-teen children (aged between 11 and 12 years; 25 girls). Attention was assessed using a six letter cancellation task and Spielberger’s State Trait Anxiety Inventory STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Of particular note, Dhanvijay and Chandan (2018) found that practicing Nadi Shuddhi 15 min a day for 12 weeks was correlated with decreased stress, heart rate, and blood pressure in first‐year medical students. Although the evidence is limited, studies have also suggested that alternate nostril breathing may help to decrease anxiety (Telles et al, 2019). For example, 15 min of alternate nostril breathing was associated with reduced anxiety in healthy young adults who participated in a public speaking simulation (Kamath et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note, Dhanvijay and Chandan (2018) found that practicing Nadi Shuddhi 15 min a day for 12 weeks was correlated with decreased stress, heart rate, and blood pressure in first‐year medical students. Although the evidence is limited, studies have also suggested that alternate nostril breathing may help to decrease anxiety (Telles et al, 2019). For example, 15 min of alternate nostril breathing was associated with reduced anxiety in healthy young adults who participated in a public speaking simulation (Kamath et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The result of this study showed that SAR brought significant stabilizing effect under the left-side-standing condition and may indicate that breathing exercises can be more helpful in maintaining balance in a more challenging situation. This could be possibly due to the attention-improving effect of breathing exercise [28] since postural control involves significant attention requirement as well as reflex or autonomic control [29]. By the same token, the right single-leg-standing would need a higher level of attention relatively than the easier bilateral standing condition (although the level may be less when compared with left-standing because it is usually the dominant side and has more abductor strength) and it may be the reason that the stabilizing effect after the SAR program was more noticeable in the right single-leg-standing than with bilateral standing.…”
Section: Discussionmentioning
confidence: 99%
“…on the effects of kapalabhati. They found kapalabhati improves cognitive performance and attention assessed through event related potentials [ 32 ], associated with decreased anxiety [ 33 ]. Similar positive outcomes were found with motor performance [ 34 ] and finger dexterity [ 35 ] and spatial and working memory tasks [ 36 ] following Kapalabhati .…”
Section: Summary Of Scientific Evidence On Yogic Cleansing Techniquesmentioning
confidence: 99%